24개월 미만 자녀를 양육하는 어머니의 스트레스와 기본심리욕구 관계에서 마사지경험 조절 효과 - 김유식(Yousik Kim); 이솔잎(Solyeep Lee) (사회과학연구논총, 2024)
연구 목적은 24개월 미만 자녀를 양육하는 어머니의 스트레스와 기본심리욕구 관계에서 마사지경험 조절 효과를 검증하는 것이다. 연구 대상은 24개월 미만 자녀를 양육하는 어머니 238명이다. 자료 처리는 SPSS 프로그램을 활용하여, 빈도분석, 탐색적 요인분석, 신뢰도 분석, 상관관계 분석, 조절회귀 분석 하였다. 결과는다음과 같다. 첫째, 24개월 미만 자녀를 양육하는 어머니의 스트레스는 기본심리욕구에 영향을 미치는 것으로 나타났다. 둘째, 24개월 미만 자녀를 양육하는 어머니의 스트레스와 기본심리욕구 관계에서 마사지경험은 조절 효과가 있는 것으로나타났다. 종합적으로, 24개월 미만 자녀를 양육하는 어머니의 어려움을 이해하고, 여가 필요성에 관한 함의를 제시하였다. This study aims to identify the moderating effect of massage experience on the relationship between stress and basic psychological needs of mother with infant. The subjects of the study were 238 mothers with baby under 24 months of age. Data processing was frequency analysis exploratory factor analysis reliability analysis correlation analysis and adjustment regression analysis with the SPSS program. First stress of mothers with infant was found to have an effect on basic psychological needs. Second, it was found that massage experience had a moderating effect on the relationship between stress and basic psychological needs of mothers with infant. Overall, the massage experience plays a role in reducing stress and increasing basic psychological needs suggesting that various ways to increase their happiness should be sought in consideration of the various situations of mothers with infant. KCI Citation Count: 0